Genomic and Transcriptome Analyses of a Thermophilic Bacterium Geobacillus stearothermophilus B5 Isolated from Compost Reveal Its Enzymatic Basis for Lignocellulose Degradation - Mengmeng Wang; Jiaxi Miao; Xuanqing Wang; Tuo Li; Han Zhu; Dongyang Liu; Qirong Shen (Microorganisms, 2020)
A lignocellulose-degrading strain isolated from thermophilic compost was identified as Geobacillus stearothermophilus B5, and found able to secrete considerable amounts of enzymes at optimal temperature (60 °C) and pH (7.5). One circular contig of 3.37 Mbp was assembled from raw data, and 3371 protein-coding genes were predicted. Clusters of orthologous groups (COG) analysis revealed various genes with functions in polymeric substrate degradation, especially for Carbohydrate Active enZymes (CAZymes), such as glycoside hydrolases (GHs) and glycosyl transferases (GTs). Furthermore, the transcriptional responses of B5 at different temperatures—with rice straw provided as the sole carbon source—were analyzed. The results revealed that B5 could resist high temperature by upregulating heat shock proteins (HSPs), enhancing protein synthesis, and decreasing carbon catabolism. Briefly, B5 possesses the ability of lignocellulose degradation, and might be considered a potential inoculant for improving composting efficiency.